Pengaruh Locus Of Control Terhadap Kesiapan Karier Mahasiswa Semester Akhir Strata satu - Muttaqien, Firdaus; Nihayah, Zahrotun (Educatio, 2025)
The problem often faced by final semester students is about uncertain employment, so they experience anxiety when they become alumni. National Statistics Agency (BPS) data on open unemployment states that in 2023 there will be around 787,973 graduates from universities who are not working. In addition to the lack of jobs for new graduates. Most of the alumni have not prepared themselves well for a career. This is the basis for the need to conduct research on the influence of locus of control on the career readiness of final semester undergraduate students at Syarif Hidayatullah State Islamic University Jakarta. The purpose is to find out the psychological condition of students before graduating from college. The research participants totalled 222 final semester students who were and had been working on their thesis. The results obtained show that there is an influence of internal locus of control on career readiness with a significant value of 0.000. While the external locus of control has no effect because the significant value obtained is 0.321. The conclusion is that the psychological condition of internal locus of control affects the career preparation of final semester students